One-step epitaxial growth of 2D nonlayered PtS on MoS2 nanograin film - Lim, Gabriel Jun Jee (Nanyang Technological University, 2020)
The discovery of two-dimensional materials (2D) has captivated significant attention in the scientific community and looks to revolutionise various electronic mediums due to their distinctive properties not found in their bulk counterparts. Most research in the field has been limited to layered crystals and are limited by their growth methods. In this work, it is demonstrated that we can go beyond the limitations of 2D materials through CVD and the growth factors considered to achieve a clean interface. Here, we report a one-step epitaxial growth of platinum sulfide (PtS) on molybdenum disulfide (MoS2) and the steps taken to characterize the fabricated material. XRD, XPS, Ramen, SEM and ADF-STEM are used to characterize the samples. The sample formed displayed a clean interface, uniformly distributed onto the MoS2 film and displayed consistent results across each characterization methods. Direct growth of these heterostructures will help researchers gain a better appreciation of these materials and expand device functionalities in potential applications.